Resumption of In-Person Classes in Public Secondary Schools Division of Zambales: Priorities and Challenges for Shared Responsibility - Antigo, Cristina L.; de Guzman, Marie Fe D (Future Science / FSH-PH Publications, 2024)
This study sought to determine the priorities for shared responsibility in Public Secondary Schools Division of Zambales for the current resumption of facetoface in-person classes for the school year 2022-2023 conducted during the third quarter among school heads of the 13 Districts of Department of Education Schools Division of Zambales, Philippines. The research design was descriptive quantitative and utilized survey questionnaire as main research instrument. This study determined that the school heads are male middle aged adults, Master's degree holders, and served in the profession for two and a half decades as Principal I and IV while the teachers are female young adults, Baccalaureate degree holders with Master’s units; served in the teaching profession for a decade as Teacher I. The school heads and teachers’ perception towards the priorities for shared responsibility was very evident in terms of Provision of Support to Teachers. Both the school heads and teachers strongly agreed that there are challenges for shared responsibility during the resumption of in-person classes in public secondary schools. The ANOVA results revealed that there was significant difference in the perception on the priorities for shared responsibility during the resumption of in-person classes in terms of school heads’ highest educational attainment and designation. There was significant difference in terms of Provision of Support to Teachers, Students’ Study Habits and Parents’ Role in Learning when attributed to teachers’ length of service. The t-Test result showed that there was significant difference between the perceptions of the school heads and the teachers on the different priorities and challenges for shared responsibility during the resumption of in-person classes in public secondary schools. The findings resulted in the development of an Action Plan to address the priorities and challenges for shared responsibility during the resumption of in-person classes; and will become a basis for DepEd Division of Zambales policy, projects and plans consideration and future implementation.